60Co and 88Y true coincidence summing correction by simulated total detection efficiency of gamma-ray spectrometry system / Ahmad Saat - Saat, Ahmad (Faculty of Applied Sciences, 2004)
A mathematical model of True Coincidence Summing (TCS) correction factors of gamma photons from simple decay schemes of °Co and 88Y was developed. The model developed made use of the total detection efficiency of the detector and the yields for the photons concerned. The total detection efficiency was determined based on the fraction of the simulated gamma photons being absorbed by the detector. Self-absorption by the sample was also taken into account. The simulation code was written in FORTRAN 90. The simulated total detection efficiencies obtained were used in the mathematical model to yield the needed TCS correction factors. The model-simulated TCS correction factors were compared with experimental results. Application of the model and simulation to samples used by other researchers shows an average agreement of within 5%.